Zika virus: out of sight but not out of the mind. Viral persistence and host responses within the central and peripheral nervous systems. Issue Volume 1(2019)Issue A (8th March 2019) - Ferguson, Debbie; Hall, Jo; Ham, Claire; Jenkins, Adrian; Giles, Elaine; Kempster, Sarah; Berry, Neil; Almond, Neil
Abstract : Following the rapid spread of Zika virus infection through the Caribbean and Americas, model systems of Zika virus infection have been established to determine disease pathology and potential health impacts for those infected with this neurotropic flavivirus. NIBSC has established both Old World (rhesus and cynomolgus macaques) and New World (red-bellied tamarins) non-human primate disease models of human Zika virus infection. Animals were infected sub-cutaneously with the Caribbean Zika isolate PRVABC59 and pairs terminated during primary viremia (3 dpc) or post clearance of plasma viremia (42 and 101 dpc). FFPE sections from multiple tissues, including brain and peripheral nerves were analysed for Zika virus RNA (RNAscope), viral proteins and host responses (immunohistochemistry). All animals became infected and rapidly cleared high levels of peripheral viremia. Zika virus RNA was detected in multiple tissues from 3 dpc with low levels of viral RNA and viral NS1 protein remaining detectable through to 101 dpc. Viral RNA was associated with both glial and neuronal cells throughout the brain and schwann cell nuclei in peripheral nerves. Neuroinflammation (astrogliosis, microgliosis, peri-vascular cuffing) and increased levels of CD3+, CD8+ or CD45+ cells were present from 3 dpc through to 101 dpc. Disruption of MAP2 neuronal dendrite staining and peripheral nerve myelin basic protein staining was also observed. The continued detection of Zika virus within tissues 3 months post infection and in the absence of a detectable peripheral viremia raises questions regarding potential long term effects of this virus and associated inflammatory responses within the nervous systems.